Study on the impact resistance of honeycomb sandwich structures under low-velocity/heavy mass. (15th October 2019) - Xue, Xinwei; Zhang, Chaofeng; Chen, Wei; Wu, Meiping; Zhao, Junhua
Abstract: The honeycomb sandwich structure is a typical light weight structure that is widely used in transportation and other industries. It is necessary to study the impact resistance of this honeycomb sandwich structure when subjected to low-velocity and heavy mass drops. To improve the impact resistance of the honeycomb sandwich structure under low-velocity and heavy load, the first stage was the development of a high ductility and high strength carbon/glass fibre hybrid composite skin. A further discussion is conducted about the relation between the honeycomb core height and the impact resistance of the honeycomb sandwich structure, according to simultaneous test results and finite element method (FEM) analysis. With the verified accurate FEM, the impact resistance of the honeycomb sandwich structure being affected by the honeycomb wall thickness, cell size and impact energy is analysed. Finally, some useful conclusions are drawn for the design of lightweight honeycomb sandwich structures.